ANALISIS PENENTUAN HARGA POKOK PRODUKSI DALAM MENETAPKAN HARGA JUAL STIK LELE POKDAKAN DESA BANGKOK KEDIRI - Yayang Dea Masuqa; Sigit Puji Winarko; Hestin Sri Widiawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The group "POKDAKAN" in Bangkok Village, Gurah District, Kediri Regency, is a new business partner, where the group "POKDAKAN" has a problem, namely the selling price of catfish sticks is still ambiguous and not in accordance with the expected results because it often occurs loss. This study aims to determine how to determine the cost of production in determining the selling price of catfish sticks by identifying the factors that influence the cost of production. Among them are the costs incurred in producing catfish sticks carried out by the group "POKDAKAN". This study involved members of the group “POKDAKAN” as respondents who were interviewed and used qualitative descriptive data analysis. This research is useful for the group "POKDAKAN" to continue to exist in running their business, because the calculation of the cost of goods plays a role in determining the selling price of catfishsticks. Keywords: Cost of goods, Selling price